Penerapan Etika Bisnis Dan Corporate Social Responsibility (CSR) Pada Usaha Kontraktor Bangunan CV. Barakallah - Ni Kadek Dwita Suardianti; Hautami Nadia Zahratul; Ghanis Bintang Desyanur; Mai Lidya; Yennita Astarini (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The application of Business Ethics and Corporate Social Responsibility has an important role in forming a company that is strong and has high competitiveness. Ethical business is the foundation of good business principles, this includes superior and sustainable business performance through compliance with applicable ethical and legal guidelines. The Corporate Social Responsibility Program is also one of the obligations that must be carried out by companies in accordance with the contents of Article 74 Paragraph 1 of Law Number 40 of 2007 concerning Limited Liability Companies. This is because, in building a business it must also provide benefits that can be felt by the business environment and society.